2017
DOI: 10.1108/prr-12-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for not changing to activity-based costing: a survey of Irish firms

Abstract: Purpose-This paper aims to report on a survey of medium and large Irish firms to ascertain reasons for not changing to more advanced costing techniques, namely, activity-based costing (ABC). Developments in technology and recent poor economic conditions would suggest that the technique could be adopted more by firms, as they make increased efforts to keep costs under control. Design/methodology/approach-A survey instrument was used to gather data drawing from the top 1,000 Irish firms. From a useable populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
0
8
0
3
Order By: Relevance
“…Furthermore, besides innovation and increased technology, the globalisation of products and services have created a competitive business environment hence, requiring data to be identified accurately and must be relevant to the cost and performance of the organisation's activities, thus the importance of the ABC method in today's environment (Ismail & Reddy, 2017). Initially, the adoption of ABC was slow due to the high expenditure involved in employing and sustaining the ABC system, however the ABC system has been used widely in countries such as the United States of America (USA) (Brierley, 2009), the United Kingdom (UK) (Al-Omiri & Drury, 2007), and Canada (Quinn, Elafi, & Mulgrew, 2017). This costing system has gained international recognition in not only developed countries but emerging economies such as China (Anderson & Young, 1999), Taiwan (Lou, Wang & Lan, 2017) and Malaysia (Ahmad, Teng, & Zabri, 2015;Maelah & Ibrahim, 2007) as they gain competitive advantages in the pursuit of globalizing their economies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, besides innovation and increased technology, the globalisation of products and services have created a competitive business environment hence, requiring data to be identified accurately and must be relevant to the cost and performance of the organisation's activities, thus the importance of the ABC method in today's environment (Ismail & Reddy, 2017). Initially, the adoption of ABC was slow due to the high expenditure involved in employing and sustaining the ABC system, however the ABC system has been used widely in countries such as the United States of America (USA) (Brierley, 2009), the United Kingdom (UK) (Al-Omiri & Drury, 2007), and Canada (Quinn, Elafi, & Mulgrew, 2017). This costing system has gained international recognition in not only developed countries but emerging economies such as China (Anderson & Young, 1999), Taiwan (Lou, Wang & Lan, 2017) and Malaysia (Ahmad, Teng, & Zabri, 2015;Maelah & Ibrahim, 2007) as they gain competitive advantages in the pursuit of globalizing their economies.…”
Section: Introductionmentioning
confidence: 99%
“…We were convinced that it would facilitate comparisons of company practice in Poland and Lithuania in terms of ABC implementation, and could contribute to modifying existing beliefs on the factors that influence the implementation process. What is more, our intention was to compare the results with research conducted in other countries Jinga et al, 2010;Wegmann, 2011;Dragija & Lutisky, 2012;Rundora & Selesho, 2014;Quinn et al, 2017). To the best of our knowledge, such a broad and comprehensive overview of ABC practice has never been performed in Polish or Lithuanian companies before.…”
Section: Methodsmentioning
confidence: 97%
“…According to the respondents, although the benefits of ABC were higher than the costs of its implementation, diffusion was low because of the perceived high implementation costs, the lack of IT resources, high labor input, the great detail of the system, and the lack of knowledge about ABC. The lack of interest in the ABC system was also studied by Clarke & Mullins (2001), ), ElGammal et al (2016, Quinn et al (2017) and Hudakova & Bajus (2015). All these studies indicated similar reasons for the slow diffusion of Activity-Based Costing, and the most frequently mentioned barriers to implementation included the high implementation and maintenance costs and insufficient knowledge of ABC among employees.…”
Section: Literature Reviewmentioning
confidence: 93%
See 2 more Smart Citations